A Bacillus thuringiensis insecticidal crystal protein with a high activity against members of the family Noctuidae. - Lambert, B (1996)
The full characterization of a novel insecticidal crystal protein, named Cry9Ca1 according to the revised nomenclature for Cry proteins, from Bacillus thuringiensis serovar tolworthi is reported. The crystal protein has 1,157 amino acids and a molecular mass of 129.8 kDa. It has the typical features of the Lepidoptera-active crystal proteins such as five conserved sequence blocks. Also, it is truncated upon trypsin digestion to a toxic fragment of 68.7 kDa by removal of 43 amino acids at the N terminus and the complete C-terminal half after conserved sequence block 5. The 68.7-kDa fragment is further degraded to a nontoxic 55-kDa fragment. The crystal protein has a fairly broad spectrum of activity against lepidopteran insects, including members of the families Pyralidae, Plutellidae, Sphingidae, and Noctuidae. A 50% lethal concentration of less than 100 ng/cm2 of diet agar was found for diamondback moth, European corn borer, cotton bollworm, and beet armyworm. It is the first insecticidal crystal protein with activity against cutworms. No activity was observed against some beetles, such as Colorado potato beetle. The protein recognizes a receptor different from that recognized by Cry1Ab5 in Ostrinia nubilalis and Plutella xylostella. In Spodoptera exigua and P. xylostella, it binds to a receptor which is also recognized by Cry1Cax but with a lower affinity. In these insects, Cry1Cax probably binds with a higher affinity to an additional receptor which is not recognized by Cry9Ca1. Elimination of a trypsin cleavage site which is responsible for the degradation to a nontoxic fragment did result in protease resistance but not in increased toxicity against O. nubilalis.